PERKEMBANGAN MOTORIK HALUS DAN MOTORIK KASAR PADA BALITA USIA 4-5 TAHUN DI PAUD DHARMA WANITA 1 DESA SINDUREJO KECAMATAN GEDANGAN KABUPATEN MALANG - Santoso, Windu; Jamilah, (Jurnal Keperawatan Bina Sehat, 2015)
Around the age of 4 years old children had mastered how to run an adult and already could run, stop and turn back. At this age children were able to stand on one leg and catch a ball which were thrown into the future. The goal of researchers was to describe the development of fine motor and gross motor skills in children aged 4-5 years in early childhood education program of Dharma Wanita 1 Sindurejo Village District Gedangan Malang Regency. Descriptive studying design. The population was all of children aged 4-5 years in early childhood education program of Dharma Wanita 1 Village Sindurejo Village District Gedangan Malang Regency as many as 20 infants and samples were taken with total sampling technique. The variables in this research was the development of fine motor and gross motor skills in children aged 4-5 years. The data was collected by observation sheet (KPSP). Then presented in the form of a frequency distribution table. The results of the studying indicated that the majority of respondents fine motor development was fit as many as 14 (70%) of the respondents and the corresponding gross motor development 12 (60%) of respondents. This happened because there were several factors affecting among other environmental factors. Based on the results of the study are expected to all parents can improve insight and knowledge about the stimulation of development so more provide a good activity or good stimulation to stimulate early childhood development and early childhood development can run normally so there is not developmental disorders.Keywords: development, fine